Hubungan Screen Time Smartphone Dengan Kejadian Obesitas Pada Masyarakat Usia 15-22 Tahun - Timotius, Timotius; Novitasari, Diana; Titanic, Pussof Yahyazucah; Chyntia, Chyntia; Ashari, Shoimatul Fitriyah (Jurnal Ners, 2024)
Smartphones are no longer necessary in everyday life. Smartphone use has been shown to have a wide-ranging impact on health. Obesity is one of the modern-day health problems that can be exacerbated by excessive smartphone use. The study's goal is to look at the link between smartphone screentime and obesity prevalence. This study's design is a cut width. Data is collected online using Google Forms (G-form). The information gathered included respondents' identities, screen times via smartphone screenshots, and degrees of obesity as indicated by height and weight measurements. There were 135 responses between the ages of 15 and 22. The bulk of respondents (83.7%) utilized cellphones for 6 hours every day. The outcomes of measuring the body mass index revealed that the majority of the respondents (71.11%) were obese. The chi-square test reveals a substantial association between screen time and metabolic health, such as obesity